AHOLI ORASIDA RATSIONAL OVQATLANISHNI TASHKIL ETISH. - Xabibullayeva Muazzam Iftixorjon qizi; Asqarova Madina Dilshodjon qizi; Akbarova Xilola Abdurasul qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Nutrition is one of the important factors that have a significant impact on health status, labor and influence of the external environment. It is said that Hippocrates said, "Rational meals must be food and medicine. The normal growth, development, healthy, and obesity to prevent diseases, Heart-viticulture, diabetes, high blood pressure and cancer shall be prevented.